THE IMPORTANCE OF SHELF PROCESSES FOR THE MODIFICATION OF CHEMICAL CONSTITUENTS IN THE WATERS OF THE EURASIAN ARCTIC OCEAN: IMPLICATION FOR CARBON FLUXES - Fransson A.; Chierici M.; Anderson L.G.; Bussmann I.; Kattner G.; Jones E.P.; Swift J.H. (My University, 2001)
Carbon transformation along the Eurasian shelves in water of Atlantic origin is estimated. Nutrient, oxygen, and inorganic and organic carbon data were used in the evaluation. By comparing the relative deficit of the different chemical constituents it is possible to evaluate the transformation of carbon. It can be seen that the chemical signature in the shelf seas was modified extensively, corresponding to an export production from the upper 50m in the Barents Sea of 28–32gCm−2, which is five times higher than that in the Kara–Laptev Seas and over the deep Eurasian basin. The difference in the export production, computed from the nutrient deficit, and the observed deficit of dissolved inorganic carbon is attributed air–sea exchange of CO2. With this approach the relative oceanic uptake of CO2 from the atmosphere was estimated to be 70% (44gCm−2) in the Barents Sea and 15% (1gCm−2) in the Kara–Laptev Seas, relative to the export production. Of the export production in the Barents Sea, about a quarter is found as DOC. The difference between the chemical signature at the Laptev Sea shelf slope and over the Lomonosov Ridge is negligible, which shows that the transformation of carbon is very small in the surface layers of the Eurasian basin. Combining the chemical transformation with reported volume transports gives an annual export production of 9.6×1012gCyr−1 in the Barents Sea. The oceanic uptake of CO2 for the same area is 9.2×1012gCyr−1.